Preparation and characterization of hybrid molecularly imprinted polymer membranes for the determination of citrinin in rice - Lee, Tien Ping; Bahruddin Saad,; Nakajima, Lisa; Kobayashi, Takaomi (Penerbit Universiti Kebangsaan Malaysia, 2019)
A new method for the determination of Citrinin (CIT) in rice samples by hybrid molecularly imprinted polymer (MIP) membrane prior to its quantification by high performance liquid chromatography with fluorescence detection (HPLC-FD) is described for the first time. Conventional extraction methods, such as liquid-liquid extraction (LLE) and solid phase extraction (SPE) produce large volumes of environmentally hazardous waste and the common sorbents used in SPE often suffered from low selectivity. Hybrid MIP membranes offer the advantage of combining the mechanical integrity of the support membrane and the selectivity of the imprinted polymer. These membranes offer large specific surfaces, providing relatively high imprinting sites per unit mass, and fine porous structures, resulting in accessibility of imprinting sites. Thus, MIPs for CIT with 1-naphthol as mimic template were prepared using divinylbenzene as crosslinker and naphthol methacrylate was hybridized into the polyethersulfone scaffold by phase inversion process. The prepared hybrid MIP membrane was characterized using Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). Using the resultant hybrid MIP membranes as sample preparation for HPLC-FD of CIT, detection and quantification limits of 0.5 ng g-1 and 1.7 ng g-1, respectively, were obtained. The intra-day and inter-day precision expressed in %RSD ranged from 1.9-2.9% and 2.6-5.9%, respectively. The recoveries of CIT in rice spiked at 5, 25 and 100 ng g-1 ranged from 89.7-94.2%. Thus, the hybrid MIP membranes can be valuable material for the practical determination of CIT in rice extracts.